Scrotal calcinosis - Hicheri, J. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2005)
Scrotal calcinosis (SC) is a rare and benign condition defined as the existence of multiple calcified nodules within scrotal skin. We report the case of a 39-year-old male patient with a three-month history of scrotal tumours that increased rapidly in number and size. Histopathological and immunohistochemical investigations showed no evidence of epithelial structure.Whether SC is idiopathic or the result of the calcification of pre-existing cysts is still a controversial issue. In some cases, as well as in our case, no evidence of cystic structure was found around calcified material, despite minutely careful studies. This suggests that SC might be truly idiopathic.
Keywords: Adult; Calcinosis; dermatologija; Diagnosis; Kalcinoza; Odrasli; Pathology; Scrotum; Skrotum; Surgery